Epigenetic Regulation of Pericentromeric Heterochromatin during Mammalian Meiosis - Khalil, A.M. (S. Karger AG, 2010)
Mammalian meiosis is a process that allows diploid progenitor germ cells to produce haploid gametes after proceeding through 2 rounds of cell divisions. The first division (MI) is unique and results in the separation of homologous chromosomes, while the second division (MII) leads to the separation of sister chromatids similar to a somatic cell division. However, the mechanisms by which meiotic cells regulate their 2 very different cell divisions are not well understood. We postulated a role for epigenetic chromatin modifications in regulating these processes. We found prior to the onset of MI that pericentromeric heterochromatic regions, which are enriched with histone H3K9me2 throughout meiosis, become enriched at late pachytene with H3S10ph and at diplotene with H4K5ace and H4K16ace, but remain underacetylated at other sites examined. RNA polymerase II, which is clearly excluded from pericentromeric heterochromatin at pachytene, becomes exclusively associated with these regions from diplotene to MI. By contrast, pericentromeric heterochromatic regions at MII are not engaged by RNA polymerase II nor enriched with H3S10ph. Furthermore, we found DICER to localize exclusively to pericentromeric heterochromatin at MI, but not MII. These results are significant since they suggest: (1) that distinct chromatin modifications differentiate the 2 meiotic divisions; (2) a role for repetitive DNA elements and RNAi in mammalian meiosis; (3) H3K9me2 is not sufficient to block RNA polymerase II elongation through heterochromatin, and (4) H3S10ph provides a ‘binary switch’ to activate transcription in heterochromatin.